Increasing Income Inequality Through Globalization And Financialization: Evidence From OECD Countries - Muhammad Budi Utama; Miftakhul Choiti (Jurnal Ilmu Ekonomi JIE, 2024)
Globalization, financialization, and digital technology are expected to help economic sectors run more effectively so that they can be distributed to a country's people, which will reduce inequality. However, this is not the case in some countries, where globalization, financialization, and digital technology can worsen income inequality. Therefore, this study aims to see how far globalization and financialization can reduce income inequality by adding the effect of digital technology. This study was conducted in 10 OECD countries for 12 years, starting from 2010-2021, and was processed using the Eviews statistical tool. The results show that globalization worsens income inequality in OECD countries, financialization can reduce income inequality, and digital technology impacts income inequality in OECD countries.